(untitled) (Acta Scientiarum. Agronomy, 2018)
The aim of this study was to validate an experimental prototype dryer with a thick-layer fixed bed and determine the quality of the dried soybean grains. The drying system was designed as a chamber with four independent drying cells, with a capacity of 164 kilograms, an air ventilation system and heating with electric heaters. This prototype was used for soybeans with an initial water content of 17% (w.b.). The samples were collected from the top, middle and bottom of the four cells to evaluate the quality of the grains. The experimental design was completely randomized factorial (3 x 4 x 3), with three temperatures settings for the drying air (30, 40, and 50°C), four drying cells and three evaluation positions (upper, middle and lower). The grains did not undergo quality changes as a function of the drying cells. In the upper part of the drying cells, there was a reduction in the specific grain mass (851 kg m-³), an increase in electrical conductivity (140.02 Î¼S cm-1 g-1), reduction in germination (63%) and oil content (7%) compared with the middle and lower dryer positions. The experimental prototype of the fixed bed dryer allowed a uniform distribution of the heated air in the drying cells, which was effective in the drying operation and in maintaining the quality of the soybean grains.